Non-specific immune responses and intestinal immunity of common carp (Cyprinus carpio) fed Jujube (Ziziphus jujube) fruit extract - Seyed Hossein Hoseinifar (2018)
© 2018 John Wiley & Sons Ltd This study investigated the effects of Jujube (Ziziphus jujube) fruit extract (JFE) as an excellent source of nutrients and phytochemicals on the innate immune responses and expression of genes involved in intestinal immunity of common carp (Cyprinus carpio) fingerlings. Three hundred healthy carps (10.78 ± 0.05 g) fingerlings were randomly allocated to 12 fibre glass tanks (300L; 15 fish per tank) and fed for 8 weeks with experimental diets which contained different levels of JFE (0%, 0.25%, 0.5%, or 1%). Thereafter, serum non-specific immune parameters [total immunoglobulin (Ig) as well as alternative complement (ACH50) and lysozyme activity (SL)] and expression of genes involved in intestinal immunity (lyz, tnf-alpha, il1b, il8, il10, and tgfb) were measured. The results revealed a significant elevation of Ig level in the JFE-fed fish (p < 0.05) over the control fish. However, there was no significant difference among treated groups in case of serum total Ig. The highest levels of SL and ACH50 were observed in fish fed 1% of JFE. Nonetheless, no significant difference was noticed regarding SL and ACH50 of control and other supplemented groups (0.25% and 0.5% JFE). Also, expression of lyz, tnf-alpha, and il1b genes increased significantly (p < 0.05) in JFE-fed fish, in a dose-dependent manner. On the other hand, significant (p < 0.05) down-regulation of il110 and tgfb were noticed in treated groups. The present findings suggested that extraction of Jujube, Z. jujube fruit, possesses beneficial effects on immune responses of common carp.